JOB INVOLVEMENT AND JOB RELEVANT INFORMATION IN MODERATING BUDGETING PARTICIPATION ON BUDGETARY SLACK - Huseno, Tun; Wati, Linda (Universitas Brawijaya, Indonesia, 2023)
Budgetary slack frequently happens in local governments. This can also occur due to indications of individual behavior lowering the income target to facilitate the achievement of local government budgets. The purpose of the study was to examine and analyze job involvement and job relevant information moderating budgetary participation on budgetary slack with empirical study on the regency of Sijunjung. The sample of this research is echelon II, III and IV officials in government of Sijunjung Regency. The sampling technique use in this study is a purposive sampling technique. The sample used in this studi were 59 respondents. The analysis of Partial Least Square (PLS) based on variance is the analytical technique used in this research. The results of the study found that budgetary participation has a positive and significant effect on the level of budget slack reduction. Job involvement was not evidenced to moderate the effect of budgetary participation on the level of budget slack reduction while job relevant information was evidenced to moderate the effect of budgetary participation on the level of budget slack reduction and is in quacy moderation. Suggestions for further research should be to examine the entire regional apparatus organization (OPD) in Sijunjung Regency to see budget slack in the budget preparation process and how employee involvement and information can reduce gaps in employee participation in budget preparation. In the participatory budgeting process, the government must consider the factors that influence budget participation, which can have an impact on budgetary slack, such as job involvement and job relevant information.